Substantiation of ways of decrease in power consumption of ropeways - Raksha, S. V.; Kuropyatnik, A. S.; Kurka, A. A. (Science and Transport Progress, 2014)
Purpose. Formation of recommendations about rational profiling of ropeways taking into account energy saving. Methodology. As criterion of power consumption the specific power of the drive as the relation of power consumption to ropeway carrying capacity is accepted. The cycle of movement of cars was conditionally divided into three stages, characteristics of each one were kinematic parameters of the ropeway. Specific power for all cycle was determined as the sum of the corresponding values by movement stages. Findings. The conducted researches showed that the specific power of the drive doesn’t depend on kinematic parameters of the ropeway. Limit value of specific power of the drive doesn’t depend on road length. With increase in capacity of cars influence of length of flight on specific power are decreased. For big length ropeways it is recommended to carry out selection of heights of supports according to features of a relief for providing minimum possible gradient of spans. Use of high-capacity cars is expedient at a ropeway construction on the district which relief is characterized by essential height differences. Long spans should be carried out as much as possible acclivous, overcoming height differences via small length spans. Originality. The new criterion of estimation of power consumption of ropeways was formulated. Practical value. The use of the received results and the formulated recommendations will allow designing ropeways with the lowered power consumption.